A descriptive study on ESL learners’ vocabulary knowledge through cognitive and metacognitive strategies - B R, Aravind; V, Rajasekaran (Universitas Ahmad Dahlan, 2020)
The present research was carried out to study the cognitive and metacognitive vocabulary learning strategies of 36 ESL learners’. Schmitt’s Vocabulary Learning Strategies questionnaire was used to conduct the study. The study revealed the subsequent array of cognitive and metacognitive strategies employed by ESL learners. Additionally, semi-structured interviews were also conducted with 10 ESL learners’ who completed the questionnaire to get more reliable information about learners’ strategies with vocabulary learning. The findings indicated that ‘Using English Language Media’, ‘Verbal repetition’, ‘Take notes in class’ were the most popular strategies, whereas ‘Skip or pass new word’ and ‘Put English labels on physical objects’ were least used. The results of this paper provide many implications for English language teaching. Detailed explanations of the participants’ cognitive and metacognitive strategies were given in the discussion.